One-Pot Difunctionalization of Aryldiazonium Salts for Synthesis of para-Azophenols - Liu, Zhenhua; Fang, Yang; Liu, Yi; Fu, Wei; Gan, Xingxing; Gao, Wen; Tang, Bo (Frontiers in Chemistry, 2022)
A novel difunctionalization of aryldiazonium salts was realized for the one-step generation of symmetric and asymmetric p-azophenols. This approach proceeded by the sequentially regioselective aromatic C-O and C-N bonds construction under mild reaction conditions, unlocking a new reaction strategy to facilitate the synthesis of p-azophenols.